Belief about Medications Among Type 2 Diabetic Patients Attending the National Diabetes Center in Iraq. - Esraa A. Hussein; Dheyaa J. Kadhim; Tawfeeq F. Al-Auqbi (College of Pharmacy University of Baghdad, 2017)
Diabetes mellitus is a common health problem worldwide counting about 1.2 million cases in Iraq in 2015. Taking in account of the patients beliefs about the prescribed medication had been reported to be one of the most important factors that affects adherence where holding positive beliefs about medications is a prerequisite for intentional adherence. The aim of the current study was to investigate and assess beliefs about medicines among type 2 diabetic patients and to determine possible association between this belief and glycemic control as well as some patient-specific factors. This study is a cross-sectional study carried out on 380 (mean age 56.58 10.06 years) already diagnosed T2DM patients who attended the National Diabetes Center, Al-Mustansiriya University Baghdad/ Iraq during December-2016 to March-2017. Belief about medicine was assessed by using an arabic version of the questionnaire. The patients had a stronger agreement with the mean necessity scale (19.29) than the mean concern scale (14.27). The majority of the patients (76.3%) had strong beliefs in the necessity of anti-diabetic treatment for maintaining good control of diabetes (scores of specific-necessity was greater than score of specific-concern). However, (18.4%) of the patients reported strong concerns about the anti-diabetic treatment (scores of specific-concern greater than score of specific-necessity). The small number of the patients (5.3%), have equal scores for specific-necessity and specific-concern scores. The patient's belief about medicine was found to be poor predictor of  good glycemic control.